2017
DOI: 10.1002/anie.201705855
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and Chemoenzymatic Three‐Step Cascades for the Synthesis of Stereochemically Complementary Trisubstituted Tetrahydroisoquinolines

Abstract: Chemoenzymatic and enzymatic cascade reactions enable the synthesis of complex stereocomplementary 1,3,4‐trisubstituted tetrahydroisoquinolines (THIQs) with three chiral centers in a step‐efficient and selective manner without intermediate purification. The cascade employs inexpensive substrates (3‐hydroxybenzaldehyde and pyruvate), and involves a carboligation step, a subsequent transamination, and finally a Pictet–Spengler reaction with a carbonyl cosubstrate. Appropriate selection of the carboligase and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 37 publications
2
84
0
5
Order By: Relevance
“…However, not only the accessible product range increases, but also the overall complexity of the reaction design. Among other aspects, major challenges in designing suitable enzyme cascades include side reactions due to enzyme‐substrate promiscuity, and balancing the different reaction steps to achieve optimal conversions and specific space‐time yields for the whole cascade. Detailed kinetic knowledge about the reactions would help, for example, in selecting the right time point at which a cascade step reaches its peak, so that the next reaction step could be started when using a sequential cascade mode (i. e. by adding the enzyme for the next reaction step).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not only the accessible product range increases, but also the overall complexity of the reaction design. Among other aspects, major challenges in designing suitable enzyme cascades include side reactions due to enzyme‐substrate promiscuity, and balancing the different reaction steps to achieve optimal conversions and specific space‐time yields for the whole cascade. Detailed kinetic knowledge about the reactions would help, for example, in selecting the right time point at which a cascade step reaches its peak, so that the next reaction step could be started when using a sequential cascade mode (i. e. by adding the enzyme for the next reaction step).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, this prevents the loss of valuable product due to sampling and analysis. In addition to the above‐mentioned advantages, NMR in general enables reaction components to be determined which can be extremely challenging to quantify with other analytical techniques, but which frequently serve as reaction components in biocatalytic synthesis, e. g. isopropylamine or acetaldehyde . The distinct advantages mentioned above, are expected to lead to an increasing relevance of NMR for applications in biotechnological systems as already indicated by the first few publications in this field …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports using recombinant NCSs from Thalictrum flavum (TfNCS), Coptis japonica (CjNCS), and Papaver bracteatum (PbNCS) have highlighted their versatility in BIA and tetrahydroisoquinoline (THIA) synthesis using arange of aldehydes and several ketones. [15][16][17][18] To date,B IAs are mainly obtained by extraction from plants.However,the yield is normally not high due to the low accumulation levels in native plant cells along with other complex metabolites and challenging isolation procedures. [12][13][14] In addition, their incorporation into enzymatic and chemoenzymatic cascades to give THIAs in high yields and stereoselectivity has demonstrated their potential in sustainable synthesis.…”
mentioning
confidence: 99%
“…[36] Interestingly,3-F-ltyrosine (9)( 2.5 mm)w as readily accepted, with an 80 % conversion yield (48 h) to give the corresponding F-DOPA analogue 12.Indeed, some previous work has indicated that 9 can be accepted by atyrosinase. [16,17,39,40] Initially,t hree cascades were developed using l-tyrosine (4,2 .5 mm ;T able 2, entries 1-3). Decarboxylated products were readily formed in all cases,g iving 14-18 in 90-100 %c onversion yields,a nd 7 was added to avoid substrate or product oxidation.…”
mentioning
confidence: 99%